What a Difference an Amino Acid Makes: An All-Atom Simulation Study of Nonameric Peptides in Inhibitory HLA-E/NKG2A/CD94 Immune Complexes - Prašnikar, Eva; Perdih, Andrej; Borišek, Jure (Frontiers in Pharmacology, 2022)
MHC class I antigen E (HLA-E), a ligand for the inhibitory NKG2A/CD94 receptor of the immune system, is responsible for evading the immune surveillance in several settings, including senescent cell accumulation and tumor persistence. The formation of this ligand-receptor interaction promotes the inhibition of the cytolytic action of immune system natural killer (NK) cells and CD8+ T cells expressing this receptor. The final outcome of the HLA-E/NKG2A/CD94 interaction on target cells is also highly dependent on the identity of the nonameric peptide incorporated into the HLA-E ligand. To better understand the role played by a nonameric peptide in these immune complexes, we performed a series of multi-microsecond all-atom molecular dynamics simulations. We generated natural and alternative variants of the nonameric peptide bound to the HLA-E ligand alone or in the HLA-E/NKG2A/CD94 complexes. A systematic study of molecular recognition between HLA-E and peptides led to the development of new variants that differ at the strategic 6th position (P6) of the peptide and have favorable in silico properties comparable to those of natural binding peptides. Further examination of a selected subset of peptides in full complexes revealed a new variant that, according to our previously derived atomistic model, can interfere with the signal transduction via HLA-E/NKG2A/CD94 and thus prevent the target cell from evading immune clearance by NK and CD8+ T cells. These simulations provide an atomistic picture of how a small change in amino acid sequence can lead to a profound effect on binding and molecular recognition. Furthermore, our study also provides new data on the peptide interaction motifs as well as the energetic and conformational properties of the binding interface, laying the structure-based foundation for future development of potential therapeutic peptides, peptidomimetics, or even small molecules that would bind to the HLA-E ligand and abrogate NKG2A/CD94 recognition. Such external intervention would be useful in the emerging field of targeting senescent cells in a variety of age-related diseases, as well as in novel cancer immunotherapies.